Pemanfaatan Media Center Paslon Sukses Dalam Membentuk Opini Publik Pada Pilkada Soppeng 2024 - Syadaruddin, Andi; Sirajuddin, Sirajuddin; Arifuddin, Arifuddin; Yusri, Yusri (KOLONI, 2025)
Direct regional head elections (pilkada) are a manifestation of the people's sovereignty to choose a leader who will form a government. The momentum of the regional elections will determine how a region will develop in the next five years. A campaign is a series of efforts made by a candidate pair to promote or fight for a particular goal to the public. Political communication is a symptom of making political interests channeled through appropriate and effective media. Through this media, political messages from candidates become one of the goals for building a political image, which is related to the formation of public opinion. Political communication actors play a role in the process of delivering and receiving political messages. Meanwhile, political messages have relevance to public resources. The SUKSES Media Center was initially to carry out personal branding for candidates. Its applies a communication planning approach by managing and disseminating political messages with the aim of a positive candidate image, namely: 1) setting goals; 2) developing various premises; 3) choosing a direction of action; 4) formulating various activities needed to translate plans into action; and 5) re-planning to correct (evaluate).